2017
DOI: 10.1139/apnm-2017-0125
|View full text |Cite
|
Sign up to set email alerts
|

Examining school-day dietary intakes among Canadian children

Abstract: Understanding how dietary intakes vary over the course of the school day can help inform targeted school-based interventions, but little is known about the distribution or determinants of school-day dietary intakes in Canada. This study examined differences between school-hour and non-school-hour dietary intakes and assessed demographic and socioeconomic correlates of school-hour diet quality among Canadian children. Nationally representative data from the Canadian Community Health Survey were analyzed using 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 39 publications
3
45
2
1
Order By: Relevance
“…shown that school meals that follow food-based standards have a higher nutrient density than packed lunches prepared at home and consumed in school (20,(43)(44)(45)(46) . This stands in contrast to findings from Canada (47) , where the nutrient density of most studied micronutrients was lower during school hours compared with meals consumed on non-school hours in a national sample of pupils. These differences might be explained by the broad variation in adherence to school nutrition guidelines and financial prerequisites across the country (47) .…”
Section: Main Findingscontrasting
confidence: 99%
See 1 more Smart Citation
“…shown that school meals that follow food-based standards have a higher nutrient density than packed lunches prepared at home and consumed in school (20,(43)(44)(45)(46) . This stands in contrast to findings from Canada (47) , where the nutrient density of most studied micronutrients was lower during school hours compared with meals consumed on non-school hours in a national sample of pupils. These differences might be explained by the broad variation in adherence to school nutrition guidelines and financial prerequisites across the country (47) .…”
Section: Main Findingscontrasting
confidence: 99%
“…Furthermore, the Canadian study assessed intake during school hours (09.00-14.00 hours), which could also have included intakes of energy-dense and nutrient-poor snacks. On the other hand, meals consumed during school hours provided significantly more vegetables to children as compared with meals consumed on non-school hours (47) .…”
Section: Main Findingsmentioning
confidence: 90%
“…Previous research has established the particular importance of energy and protein consumption in growth, and that one of the most influential factors in stunting is a child's diet. The school context provides an important opportunity to promote healthy eating, particularly among adolescents who have the poorest school-hour dietary practices [7].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have noted that CCP would not be effective in preventing students from purchasing food at nearby food retailers before or after school (21). While this may be the case, particularly for snacks, these preliminary cross-sectional results suggest an overall reduction in SSB consumption and fast food lunches during the school week; and given that at least one-third of students' total caloric consumption occurs during school hours (43,44,28), improving the lunchtime meal among youth has considerable potential to advance population nutrition.…”
Section: Discussionmentioning
confidence: 71%